Evaluación del plan de marketing de servicio como Instrumento para mejorar la fidelización de los clientes de la empresa Moda Original S.A.C. en la ciudad de Tarapoto. Periodo 2014 - Ñontol Quiroz, Susibel Juliana (2015)
This research is a compilation of data from data collection instruments, the company Fashion Original S.A.C. concerning the level of customer loyalty and use of Marketing Services as a measuring instrument; The study grew out of concern for the neglect of the strategic aspect of many micro and small business in our region, which now and this technological age is making it difficult to stay in the market, issues such as the level of satisfaction, compliance addressed with service and prices highlighting the importance of service quality as the main focus for the sustainability of the company. techniques and research tools such as surveys, forms, document analysis, signing technique were applied; of which data related to the already mentioned above were obtained. A data obtained underwent treatment; applying the method of direct, theoretical observation and practice consisting in systematic, valid and reliable record of prevention and control of risks of accidents, applying it to the manager of the company Fashion Original SAC to achieve objectives theoretical methods were applied: Analytical synthetic, abstraction, Induction and Deduction. general and specific objectives were set, which respond to conclusions that indicate the diagnosis of the current situation in which the company is also identifying the customer profile, focusing on their needs, attitudes and suggestions about the products and quality service. Designing service marketing strategies aimed at improving relationships and loyalty level that will generate customer retention and frequency of purchases. Recommending perform an internal assessment of the various factors of the company urgently needed to incorporate improvements. As the analysis of which would also be the main causes of customer dissatisfaction; in terms of strategies to remember that we live in a world increasingly competitive so you should opt for flexible and tangible strategies for the organization giving the development of research.